Banking operations : regulation, practice and treasury management - Largan, Mark.; Chartered Institute of Bankers; Institute of Financial Services (Canterbury: Chartered Institute of Bankers, 2000)
This manual is both a detailed review of the bank treasury function and a comprehensive analysis of the practices involved in control and compliance.
Previous ed.: / by Mark Largan and Alan Colley. 1997.
Includes index.
oif 30/07/15, rua 30/08/16
Loans
Keywords: Banks and banking